TYPOLOGY OF THE CHILD IMAGES IN MODERN UKRAINIAN REALISTIC PROSE FOR TEENAGERS - Качак, Т. Б. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article analyzes the figurative system of modern Ukrainian realistic prose for children. We offer the main types of child images based on the set of problematic stories (the problem of child loneliness, the relationship with parents, with peers, the problem of growing-up, love, self-fulfillment, life decision, psychological discomfort due to some complexes and/ or fears etc.), patterns of characters relation (friendship, mutual understanding/ confrontation, conflict), and different classification criteria (inner world, character, behaviour, social status etc.) So, typology of children images in modern realistic prose for teens includes the following types: a lonely child, a naughty child, a child-outsider, naughty (moody) teenager, "little adult", self-sufficient child, a strange child, problematic child.